PELATIHAN MANAJEMEN USAHA KEPADA PARA PELAKU USAHA INDUSTRI KECIL DAN MENENGAH (UIKM) KERIPIK TALAS BENENG DI KAMPUNG CINYURUP KECAMATAN KARANGTANJUNG KABUPATEN PANDEGLANG - Suhandi Suhandi; Hadi Kurniawanto; Abdul Rauf Chaerudin; Listiawati Listiawati (Jurnal Abdimas Bina Bangsa, 2022)
The majority of the residents of Cinyurup village are beneng taro farmers and entrepreneurs of beneng taro chips, but the management is still simple and is not managed systematically and wellplanned, so that it cannot provide maximum results. The aim of this training is to increase competitiveness for the small and medium entrepreneurs of taro chips into independent small industries. The method of implementation is through: seminars of material delivery, discussion, practice, mentoring, monitoring and evaluation. The results of this training show that not all small and medium industrial entrepreneurs are taro beneng chips those in Cinyurup village who have not implemented business management, have not processed distribution permits, halal certificates, produced product innovations and online marketing, due to limited funds and human resources